Towards a 'third space' community practice school-aged-care: A learning community and 'the new neighbourhood'. (May 2021) - Westoby, Peter; Cox, Laura; Cartmel, Jennifer; Roland, Brett; Treasure, Leonie; Blane, Amy; Morgan, Justin
This article explores how an organisation – Jabiru – integrates a learning 'community' philosophy into its work with children, particularly within what is understood within Australia as School-aged Care (SAC). Distinguished from other organisations, Jabiru understands community is an intentional practice that provides what we find to be a unique third space, one with links to what is sometimes understood as the new neighbourhood. Research observations and interviews in two SAC sites, guided by the conceptual framework of loving, having and being, led to key findings about the intentional approach to community that supports learning, and the significance of educator wisdom.